KESEJAHTERAAN PSIKOLOGIS PADA PASIEN PENDERITA STROKE DI KLINIK AR-ROHMAN - Deny Wiman Yahya; Faqih Purnomosidi; Anniez Rachmawati Musslifah (LPPM Universitas Sains dan Teknologi Komputer, 2023)
Psychological well-being is a condition that is expected by everyone in their life. Good psychological well-being can be seen from sufferers' ability in daily life with various rules related to their illness, such as daily medication use and food restrictions. Stroke patients with good psychological well-being can also overcome their illness because they can accept and get used to the stroke without complaining about their conditions. The study aims to find out the description of the psychological well-being of stroke patients, especially at the Ar-Rohman clinic. This research is qualitative research with a phenomenological approach. The results show that the psychological well-being of seven stroke patients at the Ar-Rohman clinic was not good because based on the six aspects of psychological well-being, there were not seen in the informants. Informants have dominant psychological well-being in the aspects of life goals and personal growth so that they become more hopeful.